VERBS WITH THE MEANING OF DESTRUCTION IN ENGLISH IN THE SEMANTIC ASPECT (American Journal of Interdisciplinary Research and Development, 2022)
The history of the development of linguistics can be represented as a change in scientific paradigms. In the middle of the last century, numerous semantic theories appeared related to the study of the formation of the meaning of language units. With the advent of such theories, various methods of analyzing meanings have arisen. All of them successfully solved particular problems, but the general problem of distinguishing between linguistic and non-linguistic knowledge, the problem of determining the boundary between dictionary and encyclopedic meaning remained unresolved. If earlier in linguistics it was considered acceptable to consider language as some kind of abstract entity, then over time it became clear that modern scientific research is impossible without the involvement of such concepts as memory, intention, action.